Political Corruption and Electoral Systems Seen with Economists’ Lenses - Dzionek-Kozłowska, Joanna (Annales. Etyka w Życiu Gospodarczym, 2014)
The ongoing process of democratisation lead to the growing importance of theelectoral systems that regulate the procedures of gaining and legitimizing power indemocracy. Taking it into account it is worth asking about the relationship betweenthese particular ‘game rules’ contained into electoral law and the respect ofthe rule of law, being one of the basic norms of a democratic system. A questionthen may be raised about the existence and the character of the relation betweenelectoral systems and the level of political corruption. It is worth noticing thatbesides the research conducted by political scientists and the representatives ofvarious branches of social sciences the significant analysis of the issue have beenpresented by the economists.In this article a brief overview of the economic studies on the relationship betweenlevel of political corruption and the electoral systems is presented so as toassess to what degree this approach may be treated as fruitful.